2018
DOI: 10.3390/ijerph15040701
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Legal Aspects of Child Sexual Abuse: A Population-Based Study in a Hungarian County

Abstract: Background: Very few studies focus on childhood sexual abuse in middle European countries. Aim: The purpose of our study is to describe the medical and legal characteristics of children who experience sexual abuse and explore common features that may result in strategies for prevention. Methods: Between 2000 and 2015, 400 girls and 26 boys under the age of 18, suspected of being sexually abused, visited one of the four hospitals in a Hungarian county. Results: Mean age at onset was 10.81 years for boys, 13.46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
4
0
2
Order By: Relevance
“…Current research into the use of multidisciplinary teams and child abuse pediatrician evaluations has primarily focused on child sexual abuse (12–16). For example, a study conducted in Hungary from 2000 to 2015 reported that 48% ( n = 205) of the 426 child sexual abuse cases reviewed had legal proceedings with only 9.6% of perpetrators ( n = 41) receiving judgments from the court (16). The closest comparable information to the current study took place in Germany which operates under a civil law system, and, as such, is not comparable to the common law system predominantly used in America (17).…”
Section: Objectivesmentioning
confidence: 99%
“…Current research into the use of multidisciplinary teams and child abuse pediatrician evaluations has primarily focused on child sexual abuse (12–16). For example, a study conducted in Hungary from 2000 to 2015 reported that 48% ( n = 205) of the 426 child sexual abuse cases reviewed had legal proceedings with only 9.6% of perpetrators ( n = 41) receiving judgments from the court (16). The closest comparable information to the current study took place in Germany which operates under a civil law system, and, as such, is not comparable to the common law system predominantly used in America (17).…”
Section: Objectivesmentioning
confidence: 99%
“…Numerous studies provide strong evidence for considering child and adolescent sexual abuse (CSA) an important global health problem. These epidemiological studies have investigated CSA in Western high-income countries and in non-Western low-and middle-income countries [1][2][3][4]. Furthermore, a large body of literature has reported the short-term and long-term consequences of CSA on both the physical and mental health of the victims [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Levando em consideração a desproporcionalidade entre os órgãos genitais de adultos e a genitália/ânus de crianças/jovens, o ato sexual com penetração nesses órgãos pode ser danoso e provocar lacerações nas vítimas, como foi observado neste estudo. Corroborando, estudos internacionais apontam a predominância de casos com lesões genitais perceptíveis, que são resultantes do contato físico entre agressor sexual e vítima 11,19,20 . Da mesma forma, a literatura científica internacional mostra que a laceração anal é um dos danos acarretados às vítimas, sendo uma evidência de agressão sexual contra crianças em tenra idade 21,22 trauma agudo e/ou hematomas, ou mesmo o rompimento do hímen, e, entre as examinadas antes das 72 após a VS, a prevalência dessas lesões foi de 21,4%, de modo que, quanto mais rápido a vítima for avaliada, maior precisão no diagnóstico 18 .…”
Section: Discussionunclassified